Production strategies for short term grow-out of the Amazon River prawn Macrobrachium amazonicum (Heller 1862) in ponds - Preto, Bruno de Lima [UNESP]; Kimpara, Janaina Mitsue [UNESP]; Moraes-Valenti, Patricia [UNESP]; Tito Rosa, Fabricio Ribeiro [UNESP]; Valenti, Wagner Cotroni [UNESP] (My University, 2011)
The aim of this study was to evaluate the effect of stocking ponds using graded and ungraded juveniles and performing drained and combined harvesting on the production of M. amazonicum. A randomized completed-blocks design with 4 treatments (farming strategies) and 3 replicates was used. Treatments were: Upper size-graded juveniles, Lower size-graded juveniles, Ungraded juveniles, all with total drained harvesting, and Combined Harvesting (ungraded juveniles). Twelve earthen ponds were stocked at 40 juveniles.m -2, according to the treatment. After 3.5 months prawns were completely harvested. Lower size-graded prawns showed smaller average weight (3.37 ± 0.25 g) than upper size-graded (4.03 ± 0.40 g) and ungraded ones (3.80 ± 0.16 g). Survival percentage varied from 68 ± 9 to 76 ± 10, productivity was slightly higher than 1,000 kg.ha -1 and apparent feed conversion rate varied from 3.0 ± 0.7 to 3.7 ± 1.3. These parameters did not differ among the farming strategies. The best strategy for short term grow-out M. amazonicum in earthen ponds is stocking ungraded juveniles and performing total harvesting by draining ponds at the end of rearing cycle. Grading juveniles before stocking and selective-harvesting managements are not advantageous because they increase costs and do not improve any production parameter.
Keywords: Amazon River prawn; Grading juveniles; Grow-out; Macrobrachium; Selective harvesting; Decapoda (Crustacea); Macrobrachium amazonicum